Towards energy security in the Inuvialuit Settlement Region: insights from community members and local residents. Issue 9 (2nd September 2021) - MacKay, Makenzie; Parlee, Brenda; Parkins, John R.
ABSTRACT: Energy security is a growing concern in the circumpolar Arctic. A growing number of Inuit and other Indigenous communities are seeking greater certainty in the sources of heat, electricity and fuel as well as alternatives to carbon-based energy systems. While top-down and large-scale approaches to renewable energy have been proposed, smaller-scale and community-based energy projects may produce greater economic and social benefits for local people, including Indigenous peoples in remote regions. Building on previous research on energy security in Indigenous and northern communities, this study shares insights about the opportunities and challenges of energy security in the Inuvialuit Settlement Region (Canada). Twenty-three interviews with a range of community members, including elders and key informants from government and industry within Inuvik and Tuktoyaktuk as well as Yellowknife, NT, highlight the energy priorities and motivations, as well as the state of community involvement in energy governance. A key challenge to improving energy security in the region stems from a perceived disconnect between the values and priorities of diverse actors and institutions involved in energy governance at the community, regional, territorial/federal levels. Recommendations include greater effort toward alignment between the many institutions, with the greatest consideration to those most vulnerable to energy insecurity at local scales.